2004
DOI: 10.1109/mei.2004.1307098
|View full text |Cite
|
Sign up to set email alerts
|

Radio engineering for wireless communication and sensor applications - Book Review

Abstract: 65This is a very handy and informative book that would be useful to polymer formulators, polymer researchers, and polymer chemists who need a convenient source for the latest information on polymeric fillers and the effects fillers have on polymer properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
10

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 0 publications
0
21
0
10
Order By: Relevance
“…In addition, related to the best use position/distance on-body, studies in [1,9] have concluded that when no body tissues are in the range of the closest space surrounding an antenna (i.e., within reactive near-field [14,15] or Wheeler's radiansphere [16]), achievable performance can be relatively close to that of up to free space. However, the boundary of the field is challenging to explain unambiguously, because of the changes in fields happen gradually [17]. Further, it should be understood that the reactive proportion of the near-field does not radiate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, related to the best use position/distance on-body, studies in [1,9] have concluded that when no body tissues are in the range of the closest space surrounding an antenna (i.e., within reactive near-field [14,15] or Wheeler's radiansphere [16]), achievable performance can be relatively close to that of up to free space. However, the boundary of the field is challenging to explain unambiguously, because of the changes in fields happen gradually [17]. Further, it should be understood that the reactive proportion of the near-field does not radiate.…”
mentioning
confidence: 99%
“…Further, it should be understood that the reactive proportion of the near-field does not radiate. Nevertheless, it is the important proportion of the radiation mechanism [17]. We assume that the most of the wearable antennas will be used in the said range, which is the content of the present paper to examine.…”
mentioning
confidence: 99%
“…In theory, a resonance frequency f res for a circuit including L n and C n can be given by the well-known equation [20] …”
Section: Equivalent Circuits For Single-and Multi-resonant Dipole Antmentioning
confidence: 99%
“…First, planar UWB dipole antenna simulation models that are redesigns of the traditional single-and multi-resonant dipole structures are designed for the frequencies of interest. Then, antenna equivalent circuit model structures to be studied are chosen based on the literature review in the previous publications [3,16,18] and common circuit theory [20]. Finally, the circuit component values are defined by following the consideration of the correspondence between equivalents and physical antenna dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…The array factor (AF) is a function of the geometry of the antenna array element and the excitation phase and it quantifies the effect of combining radiating elements in an array without the element specific radiation pattern taken into account. The array factor of an Nelement antenna array is given by (Raisanen & Lehto, 2003):…”
Section: ×8 Its Rotman Lens Microwave Bfn Design and Performancementioning
confidence: 99%